2012
DOI: 10.1172/jci58832
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 differentially regulates angiogenesis through TIE2 and integrin signaling

Abstract: Angiopoietin-2 (ANG-2) is a key regulator of angiogenesis that exerts context-dependent effects on ECs. ANG-2 binds the endothelial-specific receptor tyrosine kinase 2 (TIE2) and acts as a negative regulator of ANG-1/TIE2 signaling during angiogenesis, thereby controlling the responsiveness of ECs to exogenous cytokines. Recent data from tumors indicate that under certain conditions ANG-2 can also promote angiogenesis. However, the molecular mechanisms of dual ANG-2 functions are poorly understood. Here, we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
338
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(382 citation statements)
references
References 51 publications
21
338
2
7
Order By: Relevance
“…Considering the recent finding that YAP plays a key role in cellular mechanotransduction, it is not surprising that ANG-2 is regulated by YAP in ECs. A recent report showed that ANG-2 transcript levels are inversely correlated with EC density in vitro 22 , thus supporting our hypothesis that ANG-2 may be regulated by cell-cell contact-mediated YAP phosphorylation. Although it is still under investigation how YAP transcriptionally regulates ANG-2, our present study provides new insights into the regulatory mechanism of ANG-2 expression in ECs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Considering the recent finding that YAP plays a key role in cellular mechanotransduction, it is not surprising that ANG-2 is regulated by YAP in ECs. A recent report showed that ANG-2 transcript levels are inversely correlated with EC density in vitro 22 , thus supporting our hypothesis that ANG-2 may be regulated by cell-cell contact-mediated YAP phosphorylation. Although it is still under investigation how YAP transcriptionally regulates ANG-2, our present study provides new insights into the regulatory mechanism of ANG-2 expression in ECs.…”
Section: Discussionsupporting
confidence: 90%
“…7b-d). Similar patterns were also observed in ANG-2-neutralizing antibody-injected mice 22 . Consistently, the mRNA expression of ANG-2 was significantly reduced in Yap siRNAinjected mouse retinas (Fig.…”
Section: Yap Is Expressed In the Ecs Of The Neovascular Regionsupporting
confidence: 79%
“…Various barrier-stabilizing mediators activate Rac1, including sphingosine 1-phosphate (S1P) and angiopoietins. [58][59][60] Barrier-protective cAMP signaling activates Rac1 indirectly via the RasGTPase Rap1. 61,62 In addition, Rac1 activation downstream of thrombin promotes reassembly of cell-cell junctions during the endothelial barrier recovery phase.…”
Section: Endothelial Adherens Junction Control By Rho Gtpasesmentioning
confidence: 99%
“…First, Tie2 phosphorylation is tightly controlled by the interplay of several proteins: a paralogous receptor, Tie1; a tyrosine phosphatase, vascular endothelial-protein tyrosine phosphatase (VE-PTP); and two secreted ligands, angiopoietin (Angpt)-1 and Angpt-2, the latter of which can act as an agonist, partial agonist, or antagonist depending upon context (1)(2)(3)(4)(5)(6). Second, unlike classic growth factor receptors, Tie2 is heavily expressed and phosphorylated throughout the quiescent adult vasculature (7), suggesting that Tie2 signaling has one or more roles in vascular maintenance.…”
mentioning
confidence: 99%